Su due denti di narvalo (Monodon monoceros L. 1758) del Museo di Zoologia e Anatomia comparata dell’Università di Modena. - Ivano Ansaloni; Marisa Mari (2018)
On two narwhal teeth (Monodon monoceros L. 1758) from the Museum of Zoology and Comparative Anatomy of Modena University. There are two narwhal teeth among the finds of the Museum of Zoology and Comparative Anatomy of Modena University, whose acquisition is unknown. Their high value induce us to believe that some noble or high-ranking middle-class person bequeathed them. Archive research, carried out on the inventory of 1751 regarding the finds kept in the Medals’ Gallery of the Dukes’ Palace, discovered a narwhal tooth placed on a pedestal for show. During the French occupation of 1796, the collections of the Dukes’ Palace were looted and dispersed. Some of the paintings and bronze and marble statues were given to the school of Fine Arts, whereas the finds of naturalistic interest were donated to the Museum of Natural History of Modena University. The best paintings, precious coins, cut gems etc. were sent to France. After the Restauration, Duke Francesco IV presented most of the naturalist finds that had been taken away to the Museum of Natural History. Among these finds, there was also the narwhal tooth previously described. There are no data about another narwhal tooth, although it probably belonged to the Duke’s collections and was kept in another part of the palace or in another residence.